The Inland Revenue - Johnston, Alexander (London: George Allen & Unwin Ltd., 1965)
This book describes the organization and functions of the Inland Revenue Department as the stood at the beginning of 1965. The organization, however, is continually being adapted to changing conditions.
Includes index.
ne 6/05/2018
Loan
Keywords: Inland revenue; Tax rates; United Kingdom